The design and synthesis of antituberculosis peptidomimetics focusing on lassomycin derivatives - Ngqinayo, Ntombizanele (My University, 2019)
Tuberculosis (Tb) is a disease ranked among the top ten causes of death worldwide and is responsible for infecting around 10 million people each year. Tb is caused by the Mycobacterium Tuberculosis (M. tb) bacterial pathogen. The mycobacterium has become resistant towards currently approved drugs which mostly target the cell wall and this has led to the development of the multidrug resistant (MDR) and extremely drug resistant (XDR) M. tb strains. The resistant strains are difficult to treat and require longer treatment duration with the use of combinatory drugs that result in a number of serious side effects. These limitations have led to the search for novel anti-Tb agents and the discovery of lassomycin, an antimicrobial peptide (AMP) that utilizes a different mode of action. The peptide targets the caseinolytic protease of M. tb which is essential for cell survival and causes uncontrolled protein unfolding which results in cell death. Lassomycin is a 16amino acid long basic peptide isolated from a soil bacteria, Lentzea kentuckyensis sp. that been found to be highly selective and potent towards M. tb without affecting mammalian cells.2 The objectives of this project are (i) to modify lassomycin into drug-like derivatives by incorporating N-methylated amino acids to make the peptide more stable against enzymatic degradation; (ii) to shorten the synthetic route by replacing the lactam bridge with a disulfide bridge; (iii) to replace the arginine amino acids in the peptide sequence (difficult to couple) with lysine amino acids to investigate the role of arginine in the binding of the peptide to the acidic region of the caseinolytic enzyme; and (iv) to make the peptide more cationic to improve selectivity for the negatively charged bacterial membrane by adding lysine residues. Peptides were synthesized via the fmoc solid phase peptide synthesis strategy; purified using a semi-preparative High Performance Liquid Chromatogram (prep-HPLC) and analyzed using High Performance Liquid Chromatography Mass Spectrometry (HPLC-MS) and nuclear magnetic resonance (NMR) spectroscopy. The bactericidal activity of selected lassomycin derivatives against M. tb was determined using the Alarmar blue assay and one of the derivatives showed a bactericidal effect at a concentration of 9.87 µg/ml which is comparable to that of ethambutol. The derivatives were also found to be selective for pathogens that share a similar protease to that of the M. tb such as Bacillus Subtilis (B. subtilis) and inactive against other pathogens that do not contain the protease. The 3-dimensional structure of the active derivatives will be determined in the future using NMR spectroscopy.
A dissertation submitted in partial fulfilment of the requirement for the degree of Master of Sciences to the Faculty of Sciences, University of the Witwatersrand, Johannesburg, 2019
Keywords: Mycobacterium tuberculosis; Tuberculosis, Pulmonary